NOVEL ANALYSIS (80S-90S) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In the 80 s and 90 s, active critics expanded the means of expressing the character's point of view, and the types of artistic speech, about twenty types and forms, brought the speech process to the stage of formation. Such aspects as the introduction of the character’s point of view and the stream of consciousness into the author’s statement were observed. The article gives comments on the study of the novel of the 80 s and 90 s.